Chalcogen Bonding due to the Exo-Substitution of Icosahedral Dicarbaborane - Fanfrlík, Jindřich; Hnyk, Drahomír; Hobza, Pavel (Molecules (Basel, Switzerland), 2019)
Chalcogen atoms are a class of substituents capable of generating inner and outer derivatives of boron clusters. It is well known that chalcogenated boron clusters can form strong σ-hole interactions when a chalcogen atom is a part of an icosahedron. This paper studies σ-hole interactions of dicarbaboranes with two exopolyhedral chalcogen atoms bonded to carbon vertices. Specifically, a computational investigation has been carried out on the co-crystal of (1,2-C2B10H10)2Se4•toluene and a single crystal of (1,2-C2B10H10)2Te4.
Keywords: borany; heteroborane; sigma hole; Crystallization; Thermodynamics; molekulární modely; chalkogeny; Chalcogens; co-crystal; statická elektřina; Boranes; Models, Molecular; termodynamika; krystalizace; Static Electricity